The Accuracy of Job Seekers' Wage Expectations - Marco Caliendo; Robert Mahlstedt; Aiko Schmeißer; Sophie Wagner (Institute of Labor Economics (IZA), 2024)
We study the accuracy of job seekers' wage expectations by comparing subjective beliefs to objective benchmarks using linked administrative and survey data. Our findings show that especially job seekers with low objective earnings potential and those predicted to face a penalty compared to their pre-unemployment wage display overly optimistic wage expectations. Moreover, wage optimism is amplified by increased job search incentives and job seekers with overoptimistic wage expectations tend to overestimate their reemployment chances. We discuss the labor market implications of wage optimism, as well as the role of information frictions and motivated beliefs as sources of overoptimism.
Keywords: D83; D84; J64; 330; subjective expectations; objective benchmarks; job search; unemployment; reemployment wages